The concept of abuse in EU competition law : law and economic approaches / Pınar Akman. - Akman, Pinar. (Hart, 2012)
Using law and economic approaches, this book explores the possible objectives of Article 102 TFEU and proposes a modern approach to interpreting abuse, focusing analysis on the notion of exploitative abuse and how to deal with it in situations of excessive pricing and discrimination.